Aktivitas Antibakteri dari Kulit Buah Mundar (Garcinia forbesii) - Hayatun Izma; Muhammad Ikhwan Rizki; Khoerul Anwar; Dyah Anggraeni; Satrio Wibowo Rahmatullah; Aditya Maulana Perdana Putra; Dita Ayulia Dwi Sandi (JURNAL FARMASI DAN MAKANAN, 2023)
Garcinia forbesii is traditionally used as medicine and cosmetics. The aimed was to determine antibacterial activity of ethanolic extract and fraction of Garcinia forbesii pericarp against Staphylococcus aureus and Propionibacterium acne based on the diameter of inhibition zone, the minimum inhibitory concentration (MIC) and the minimum killing concentration (MBC). The results showed that the largest inhibition zone diameter against Staphylococcus aureus and Propionibacterium acne was indicated by ethyl acetate fraction of 5.08Â±1.020 mm and 14.33Â±3.326 mm. The MIC value of ethanol extract against Staphylococcus aureus and Propionibacterium acne bacteria was >1.5%, n-hexane and ethyl acetate fraction had the same results, namely against Staphylococcus aureus >1.5% and Propionibacterium acne at 1.5%. The MBC value was only obtained for fraction samples of Propionibacterium acne at concentration of 1.5%. It was concluded that ethyl acetate had strong antibacterial activity against Propionibacterium acne based on the value of inhibition zone diameter, MIC, and MBC.